Gambaran Budaya Batak dalam Novel Terminal Cinta Terakhir Karya Ashadi Siregar: Antropologi Sastra - M, Asia; Ridwan, Ridwan; Rembon, Earline Griselda (Nuances of Indonesian Language, 2024)
The aim of this research is to find out what Batak culture is in the novel Terminal Cinta Akhir by Ashadi Siregar. The type of research used is qualitative research. In this research, data collection techniques were carried out using library techniques. This research data analysis technique was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The novel Terminal Cinta Terakhir is studied using literary anthropology studies. The results of the research show that there are several Batak cultures contained in the novel Terminal Cinta Terakhir. Even though the story is set in Jakarta, Batak culture is well depicted in the novel. Batak culture in the novel exists in several aspects, namely cultural context, human and environmental interaction, identity and identification, and popular culture.